1989
DOI: 10.1080/01919518908552431
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Carbonyl Compounds in Ozonated Water by the PFBOA Method

Abstract: PFBOA, O-(2,3,4,5,6-pentafluorobenzyl)hydroxylamine, is excellent as a derivatizing agent in the GC determination of carbonyl compounds in ozonated water samples.Surface and waste waters have been ozonated.The carbonyl ozonation by-products were identified as PFBOA derivatives by gas chromatography-mass spectrometry. The main by-products of ozonation identified were formaldehyde, glyoxal, methylglyoxal, and 13 other compounds. The characteristics of the first three compounds with respect to production and deco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 9 publications
2
35
0
1
Order By: Relevance
“…Yamada and Somiya (7), by using an o- (2,3,4,5,6,-pentafluorobenzyl)-hydroxylamine (PFBOA) derivatization method were able to demonstrate the presence of low molecular weight aldehydes in ozonated surface and wastewater. Their study revealed that formaldehyde and acetaldehyde are the major carbonyl by-products present in ozonated waters.…”
Section: Introductionmentioning
confidence: 99%
“…Yamada and Somiya (7), by using an o- (2,3,4,5,6,-pentafluorobenzyl)-hydroxylamine (PFBOA) derivatization method were able to demonstrate the presence of low molecular weight aldehydes in ozonated surface and wastewater. Their study revealed that formaldehyde and acetaldehyde are the major carbonyl by-products present in ozonated waters.…”
Section: Introductionmentioning
confidence: 99%
“…A formação de aldeídos pelo processo de ozonização das águas de abastecimento está bem estabelecida (LANGLAIS et al, 1991;MELIN & ODEGAARD, 2000;HUANG et al, 2005 O método aplicado para determinar as moléculas de baixo peso molecular dos compostos carbonílicos na água usando O-(2,3,4,5,6-pentafluorobenzil hidroxilamina hidrocloreto -PFBOA-HCl) como agente derivatizante, originalmente foi descrito por Yamada & Somiya (1989) e aperfeiçoado por Glaze et al (1989) Para avaliar a existência, ou não, de diferenças significativas entre os valores médios de pH, DQO, concentrações de formaldeído, acetaldeído e glioxal metilglioxal, e eficiência de inativação para coliformes fecais e E. coli, empregou-se o método estatístico para "comparação de médias de duas amostras" (MILLER & MILLER, 1993). De acordo com os dados reportados na literatura, a eficiência na desinfecção por ozonização é pouco afetada para os valores de pH entre 6,0 e 8,0 (LANGLAIS et al, 1991;SILVA et al, 2007;2010;2011).…”
Section: Parâmetrounclassified
“…The method used for the determination of carbonyls using O (2, 3, 4, 5, 6 -pentafluorobenzyl) hydroxylamine hydrochloride (PFBOA.HCl) as a derivatizing agent was originally described by Yamada & Somiya (1989) and was improved by Glaze et al (1989). This method is recommended by the US Environmental Protection Agency (method 554.1) for analysis of carbonyl compounds in water.…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers have shown that the aldehydes production increases with the increasing of ozone dosage and contact time (Glaze et al, 1989;Yamada & Somiya, 1989); whereas the others reported that a further increase of ozonation time would reduce the aldehydes formation (Gracia et al, 1996;Ko et al, 1998, Silva 2010.…”
Section: --Introductionmentioning
confidence: 99%